2019
DOI: 10.1002/chem.201903128
|View full text |Cite|
|
Sign up to set email alerts
|

Unlocking the Drug Potential of the Bryostatin Family: Recent Advances in Product Synthesis and Biomedical Applications

Abstract: Bryostatins are a class of naturally occurring macrocyclic lactones with a unique fast developing portfolio of clinical applications, including treatment of AIDS, Alzheimer's disease, and cancer. This comprehensive account summarizes the recent progress (2014–present) in the development of bryostatins, including their total synthesis and biomedical applications. An emphasis is placed on the discussion of bryostatin 1, the most‐studied analogue to date. This review highlights the synthetic and biological challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 111 publications
(109 reference statements)
0
36
0
Order By: Relevance
“…Bryostatins possess antitumor activity and immune modulatory properties, and also been demonstrated to be able to enhance memory and learning [ 56 ]. Bryostatin-1, a macrolide lactone with 11 chiral centers, is a potent modulator of PKC, a multifunctional protein responsible for cell differentiation and signal transduction [ 57 ]. Of the family of PKC isozymes, it was found that PKCε was involved in learning and memory and was deficient in fresh frozen hippocampal brain samples from AD patients [ 55 ].…”
Section: Marine Natural Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bryostatins possess antitumor activity and immune modulatory properties, and also been demonstrated to be able to enhance memory and learning [ 56 ]. Bryostatin-1, a macrolide lactone with 11 chiral centers, is a potent modulator of PKC, a multifunctional protein responsible for cell differentiation and signal transduction [ 57 ]. Of the family of PKC isozymes, it was found that PKCε was involved in learning and memory and was deficient in fresh frozen hippocampal brain samples from AD patients [ 55 ].…”
Section: Marine Natural Productsmentioning
confidence: 99%
“…Bryostatin-1 activates PKCε by binding to the N -terminus C1 domains of PKC causing autophosphorylation, protein translocation, and ubiquitination of PKC, thereby downregulating the protein. The normal levels are restored by de novo synthesis of the protein [ 52 , 57 ]. The activation of PKCε causes degradation of Aβ, activation of α-secretase, generating the synaptogenic non-toxic soluble amyloid-β protein precursor α and reduction of GSK3-β activity, thus decreasing hyperphosphorylation of tau [ 55 ].…”
Section: Marine Natural Productsmentioning
confidence: 99%
“…Bryozoan metabolites exhibiting in vitro anticancer properties were comprehensively and recently reviewed by Pejin et al [111], Wu et al [11], Tian et al [10], and Figuerola and Avila [12]. Bioactive bryozoan metabolites were also discussed by Skropeta and Wei [112] reviewing advances in deep-sea natural product research, as well as by Hegazy et al [113] reviewing biomedical leads from Red Sea marine invertebrates.…”
Section: Bryozoans As Sources Of Novel Anticancer Drugsmentioning
confidence: 99%
“…To overcome these hurdles, several approaches can be actuated, including marine invertebrate aquaculture, synthesis, partial synthesis, and symbiont culture, all of which strongly depend on the biology of the producing organisms and on the true origin of the bioactive compounds. Tian et al [10] and Wu et al [11] already comprehensively reviewed this topic. Below, we outline our perspectives on these crucial aspects that are hoped to enable bryozoan metabolites to be used in human medicines.…”
Section: Sourcing Of Bryozoan-derived Compounds Of Medicinal Interestmentioning
confidence: 99%
See 1 more Smart Citation